Answer:
237
Step-by-step explanation:
multiply the length value by 10
Answer:
-2, 3, -0.5 + 0.866i, -0.5 - 0.866i.
Step-by-step explanation:
As the last term is -6 , +/- 2 , +/- 3 are possible zeroes.
Try 2:-
(2)^4 - 6(2)^2 - 7(2) - 6 = -28 so 2 is not a zero.
3:-
(3)^4 - 6(3)^2 - 7(3) - 6 = 0 so 3 is a zero.
(-2)^4 - 6(-2)^2 - 7(-2) - 6 = 0 so -2 is also a zero.
Divide the function by (x +2)(x - 3), that is x^2 - x - 6
gives x^2 + x + 1
x^2 + x + 1
So we have x^2 + x + 1 = 0
x = [-1 +/- √(1^1 - 4*1*1)] / 2
= -1 + √(-3) / 2 , - 1 - √(-3) / 2.
= -0.5 + 0.866i, -0.5 - 0.866i
I believe the answer is (-1,1) . The origin is the same as (0, 0) so I drew the line on a quick graph and if you are talking about distance, then the answer should be correct.
Hope this helped :)
Answer:
12cm and 16cm
Step-by-step explanation:
The hypotenuse of the right angle triangle = 20cm
let the other two sides be x and y;
The difference;
x = y - 4
Problem:
Find x and y;
Solution:
According to the pythagoras theorem;
x² + y² = 20² ------ i
x² + y² = 400 ----- i
and x - y = 4 ---- ii
So; x = 4 + y
Now input the value into equation (i);
(y + 4)² + y² = 400
(y+4)(y+4) + y² = 400
y² + y² + 4y + 4y + 16 = 400
2y² + 8y + 16 = 400
2y² + 8y + 16 -400 = 0
2y² + 8y - 384 = 0;
y² + 4y - 192 = 0
Factorize the equation;
y² + 16y - 12y - 192 = 0
y(y + 16) - 12(y + 16) = 0
(y-12)(y + 16) = 0
y -12 = 0 or y+ 16 = 0
y = 12 or -16
It is not realistic for the length of a body to be a negative value, so y= 12;
since;
x - y = 4,
x = 4 + 12
x = 16
$13.53 is the answer to you problem